New impedance-based fault location method for unbalanced power distribution systems - Alwash S.F.; Ramachandaramurthy V.K. (John Wiley and Sons Ltd, 2023)
Electric fault location; Location; Software testing; Conventional methods; Distribution lines; Distribution systems; Impedance based methods; Power distribution faults; Power distribution system; Power system protection; Unbalanced distribution systems; Electric power system protection